Otimizando com a versátil sequência de Fibonacci - Araújo Filho, José Américo Rodrigues (1989)
There have been many applications of the Fibonacci sequence in various areas of knowledge, such as architecture, economics, mathematics, as well as the finding of its presence in certain biological behaviors. In optimization, this sequence has been used to obtain optimal point-in-function approximations (problems without restrictions). In the particular case of a variable, Kiefer J. [7] wrote an article in which he states that the best result is obtained when we use the Fibonacci search algorithm (based on the sequence quoted above). The purpose of my paper is to present some of the Fibonacci sequence (Chapter 1) and make the work of Kiefer quoted earlier (Chapter 2) more accessible to non-optimization specialists.